Regulation in Hungary of the Use of Waste Water and Sewage Sludge in Agriculture - Horváth, Imre (Acta Agraria Debreceniensis, 2004)
Regulating the use of waste water and sewage sludge in agriculture in such a way as to prevent harmful effects on soil, vegetation, animals and man.In European Union there is a Council Directive (86/278/EEC) on the protection of the environment, and in particular of the soil, when sewage sludge is used in agriculture.In the enlargement process of the European Union the Hungarian Government created a new rule (50/2001. (IV. 3.) Government regulation) which regulate using of waste water and sewage sludge in agriculture. This Hungarian rule is legal and reconcilable with the Council Directive.The Regulation lays down limit values for concentrations of heavy metals in the soil, in waste water, in sludge and for the maximum annual quantities of heavy metals which may be introduced into the soil.Waste water, sludge and soil on which it is used must be sampled and analysed.Sewage sludge must be treated for six months before being used in agriculture.The use of waste water and sludge prohibited on grassland, on nature reserved areas, in ecological farming, and soil in witch fruit and vegetable crops are growing, with the exception of fruit trees.The states soil conservation authority must keep records registering the following:– the quantities of waste water and sludge produced;– the composition and properties of sludge;– the type of treatment carried out;– the names and addresses of the recipients of the sludge and places where the sludge is to be used.The Government every four years must prepare a consolidated report on the use of sludge in agriculture, specifying quantities used, criteria followed and any difficulties encountered. This report must be forwarded to the Commission.Last but not least in the light of Member States reports, the Commission will if necessary submit appropriate proposals for increased protection of the soil and the environment.